Chrysophanol inhibits of colorectal cancer cell motility and energy metabolism by targeting the KITENIN/ErbB4 oncogenic complex - Mücahit Varlı; Eunae Kim; Songjin Oh; Sultan Pulat; Rui Zhou; Chathurika D. B. Gamage; Barış Gökalsın; Nüzhet Cenk Sesal; Kyung Keun Kim; Man-Jeong Paik; Hangun Kim (Cancer Cell International, 2024)
Abstract Background Expression of the KITENIN/ErbB4 oncogenic complex is associated with metastasis of colorectal cancer to distant organs and lymph nodes and is linked with poor prognosis and poor survival. Methods Here, we used in vitro and in silico methods to test the ability of chrysophanol, a molecule of natural origin, to suppress the progression of colorectal cancer by targeting the KITENIN/ErbB4 complex. Results Chrysophanol binds to ErbB4, disrupting the ErbB4/KITENIN complex and causing autophagic degradation of KITENIN. We demonstrated that chrysophanol binds to ErbB4 according to a molecular docking model. Chrysophanol reversed KITENIN-mediated effects on cell motility, aerobic glycolysis, and expression of downstream effector genes. Moreover, under conditions of KITENIN overexpression, chrysophanol suppressed the production of onco-metabolites. Conclusion Chrysophanol suppresses oncogenic activities by targeting the KITENIN/ErbB4 complex. Graphical Abstract